Evaluación de parámetros reproductivos en cinco grupos de gallinas criollas en el barrio prado alto, parroquia Malacatos - Paltin Saraguro, Sonia Alexandra (2016)
The objective of this research was to evaluate the reproductive parameters (percentages of fertility, infertility, mortality and births) through natural incubation. The objective of this research was to evaluate reproductive parameters in five groups of hens in El Barrio Prado Alto, Malacatos Parish. In the methodology the scientific, Inductive, Analytical and deductive methods were used. The techniques employed were: direct observation, study variables were fertility, infertility, mortality, births in relation to fertile eggs and profitability in T1, T2, T3, T4, and T5 treatments. Field research lasted 35 days. We used 5 treatments, 3 replicates with 2 experimental units, giving a total of 30 hens. The management of the hens was semi-intensive, receiving all the same conditions of handling and feeding. The evaluation of the reproductive parameters of the hens was based on descriptive statistics. The results obtained were as follows: The highest percentage of fertility of eggs is 90% in T4 and T5 and lastly T3 in 80%. The highest percentage of infertility is 20% in T3, followed by T2 with 13.3%, and in the last place the T4 AND T5 with 10% respectively. The highest percentage of mortality occurred in T3 with 10%, and T2 with 1.7%, while in the remaining treatments there was no mortality. The highest percentage of births of live chickens was in the treatments: T4 and T5 with 80%, followed by T2 and T3 with 70% last. The best average of births in relation to fertile eggs is in T4 and T5, with 89% and lastly T3 with 86%. And finally, the profitability in the treatments: T4 and T5 was 34% and The lowest with 24% as conclusions The best average of the births in relation to the fertile eggs was of the treatments: four and five, with 89%. As recommendations Use eggs for incubation less than one week of laying to achieve 100 percent of births. I conclude that the production of Creole hens contributes greatly to the feeding of families and is part of the family economy